The Effect of the Reactor Type on the Selectivity of Thermal Reactions of p-Xylene in Temperature Gradient Systems - Kawakami, Shigenobu; Iwaki, Shingo; Nakada, Masahiro; Yamaguchi, Tatsuaki (Bulletin of the Chemical Society of Japan, 1991)
Thermal reactions of p-xylene were investigated in two kinds of reactors, batch type and flow type, with a large temperature gradient. Excellent differences of the resulting products were observed between these two types of reactors. As for a batch type reactor, 4,4′-dimethylbibenzyl was produced in a high yield with [2.2]paracyclophane and toluene as by-products, and as for a flow type reactor, toluene was obtained as a major product with a low selectivity of 4,4′-dimethylbibenzyl, respectively. These results were different from those of the conventional fast flow pyrolysis method in which [2.2]paracyclophane or poly(3,6-dimethylene-1,4-cyclohexadiene) was formed as a major product. These differences can be accounted for by the partial separation of a reaction mixture caused by the thermal diffusion effect, which arises when the mixture is subject to a temperature gradient.